Single-cell/spatial integration reveals an MES2-like glioblastoma program orchestrated by immune communication and regulatory networks - Zhang, Chonghui; Tan, Lu; Zheng, Kaijian; Xu, Yifan; Wan, Junshan; Wu, Jinpeng; Wang, Chao; Guo, Pin; Feng, Yugong (Frontiers in Immunology, 2025)
BackgroundGlioblastoma (GBM) exhibits marked plasticity and intense microenvironmental crosstalk. We aimed to delineate mesenchymal programs with spatial resolution, clinical relevance, and mechanistic anchors.MethodsWe integrated single-cell RNA-seq, bulk transcriptomes, and Visium spatial data. After rigorous QC and Harmony integration, we annotated 12 cell states using canonical markers, decoupler-based ORA, and AUCell. Tumor boundaries were defined by inferCNV/CopyKAT; developmental potential by CytoTRACE2 and PHATE. Post-translational modification (PTM) axes were scored from curated gene sets. A cell type-aware GNN linked bulk expression to a patient-similarity graph for survival modeling and gene-level hazard attribution. Network convergence combined bulk WGCNA (TCGA/CGGA), single-cell hdWGCNA, BayesPrism deconvolution, and external GEO validation. Ligand–receptor (LR) signaling was inferred with LIANA+, embedded in a signed causal network, and mapped spatially. ARRDC3 expression was assessed in GBM tissues; U251 gain- and loss-of-function assays evaluated proliferation and migration.ResultsWe resolved major GBM states, including two mesenchymal programs (MES1-like, MES2-like). CNV-high regions marked malignant cores, and CytoTRACE2 identified high-potency niches within MES2-like and Proliferation states along non-linear trajectories. PTM landscapes segregated by state; S-nitrosylation, glycosylation, and lactylation were enriched in mesenchymal programs. A GNN risk score stratified overall survival in TCGA (n=157) and generalized to CGGA-325 (n=85) and CGGA-693 (n=140). MES2-like abundance remained an independent adverse predictor (HR = 2.31; 95% CI, 1.04–5.10). MES2-high tumors upregulated EMT, TNFα/NF-κB, JAK/STAT, hypoxia, angiogenesis, and glycolysis; S-nitrosylation associated with increased hazard. Cross-modal convergence defined a conservative MES2 core enriched for ECM remodeling, collagen modification, focal adhesion, and TGF-β regulation. LR analysis prioritized a TAM-to-MES2 axis (e.g., GRN–TNFRSF1A, ADAM9/10/17–ITGB1, TGFB1–ITGB1/EGFR) converging on a CEBPD-centered module. Spatial mapping localized MES2 hotspots within CNV-defined territories and revealed a TNFRSF1A–CEBPD–ARRDC3 focus at an infiltrative rim. ARRDC3 was upregulated in GBM tissues; in U251 cells, knockdown promoted and overexpression suppressed proliferation and migration, indicating context-dependent roles.ConclusionsMES2-like GBM is an ECM-driven, stress-adapted state with strong prognostic impact. We nominate CEBPD and TNFRSF1A/ITGB1 as actionable nodes and identify ARRDC3 as a spatially restricted effector with context-dependent tumor-modulatory functions warranting therapeutic exploration.